Molluscan diversity along a Mediterranean soft bottom sublittoral ecotone - Panayota Koulouri (Scientia Marina, 2006)
Molluscan diversity associated with sublittoral soft-bottoms was studied in Heraklion Bay as part of a long-term multidisciplinary research programme in the coastal environment of northern Crete (eastern Mediterranean). Quantitative benthic samples were collected in a pilot survey from a grid of 28 stations, followed by a seasonal sampling carried out over a seven- station transect located from 10 to 40 m depth. Univariate and multivariate analyses indicated the presence of a clear zonation along the depth gradient for the molluscan fauna and three main associations were identified in bathymetric zones parallel to the coastline. The structure of the local molluscan communities revealed the existence of an extended transition zone (ecotone) between a shallow sandy association and a deeper muddy one and a functional pattern, based on the feeding guilds, was evident along the environmental gradient. Application of graphical techniques, by using molluscan taxocoenosis, indicated a rather naturally disturbed habitat. Beta-diversity measures indicated different seasonal community adaptations to the prevailing environmental conditions. Results derived from this study revealed that beta-diversity may be a good descriptor for the assessment of the strength and breadth of sublittoral transition zones along environmental gradients.